High-strength magnesium alloy for improving tension-compression asymmetry and preparation method thereof
By adding Zn, Bi and Co elements to the magnesium alloy and adopting hot extrusion and solid solution aging treatment processes, the problems of tension asymmetry and poor room temperature molding performance of magnesium alloys are solved, and the preparation of magnesium alloys with high strength and low tension asymmetry is achieved, which simplifies the process and reduces the cost.
Patent Information
- Application Number
- CN202510134324.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Magnesium alloys have significant tension asymmetry and poor room temperature molding performance when used, which limits their wide application in structural parts.
A high-strength magnesium alloy was prepared by rational addition of Zn, Bi and Co elements, combined with the process steps of hot extrusion and solid solution aging. The components of the alloy include a Zn element content of 5.5% to 6.5%, a Bi element content of 2.5% to 3.5%, a Co element content of 0.5% to 0.7%, and a tension and pressure asymmetry are improved through specific heat treatment steps.
The high strength and low tension asymmetry of magnesium alloys are achieved, the process steps are simplified, the preparation cost is reduced, the production efficiency is improved, and the application range of Mg-Zn-based alloys is expanded.
Smart Images

Figure CN119553158A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy materials, and in particular relates to a high-strength magnesium alloy with improved tension-compression asymmetry and a preparation method thereof. Background Art
[0002] Magnesium and its alloys are the lightest metal structural materials (density is about 1.74g / cm 3 , which is 2 / 3 of aluminum and 1 / 4 of iron), has the advantages of high specific strength and stiffness, easy processing, earthquake resistance, good electromagnetic shielding performance and recyclability. As my country has abundant magnesium reserves, and under the background of vigorously advocating lightweight, energy conservation and emission reduction, magnesium alloys have bright prospects in transportation, aerospace and other fields.
[0003] However, the application field of magnesium alloys is still far less than that of aluminum alloys and steel, and the commercialization process is hindered. The fundamental reason is that magnesium alloys still have significant defects in application. First of all, magnesium alloys have a hexagonal close-packed crystal structure. This structure can provide relatively few independent slip systems for plastic deformation at room temperature. Even if the material may adapt to deformation through twinning, the twinning effect is also very limited, resulting in poor room temperature forming performance; and in the close-packed hexagonal crystal structure of magnesium alloys, the crystal symmetry is low and the tensile and compressive asymmetry is serious, making it unsuitable for use as a structural part. These problems have greatly hindered the widespread application of magnesium alloys. Therefore, there is an urgent need to find a magnesium alloy system and a preparation method that can improve the tensile and compressive asymmetry of magnesium alloys and improve their strength. At present, the significant tensile and compressive asymmetry of magnesium alloys is generally improved by adding alloying elements and designing heat treatment processes. Patent CN201310144920.6 "An induction heat treatment process for reducing the tension and compression asymmetry of magnesium alloy materials" proposes to first apply a certain amount of compressive pre-deformation along the main deformation direction of extrusion and rolling, and then use induction heating and quenching methods to improve the tension and compression asymmetry of the alloy through the twin deformation characteristics, but the tensile and yield strengths prepared by this invention method are very low, and it is difficult to be widely used in the main load-bearing structural parts. Patent CN202110520025.4 effectively improves the tension and compression asymmetry of the alloy through secondary extrusion molding, and improves the yield strength and tensile strength of the alloy by adding rare earth elements, but the invention method has a high rare earth content and the improved mechanical properties are limited, which increases the production cost and limits its wide application. Mg-Zn alloy is a typical aging precipitation alloy. Due to its high aging hardening efficiency, it is considered to be one of the most promising heat-treatable strengthening alloys. However, the single Mg-Zn binary alloy has not been applied in engineering due to its large crystallization temperature range, poor casting performance, hot cracking and serious tension and compression asymmetry. Therefore, it is of great significance to develop a magnesium alloy with low rare earth or no rare earth, higher mechanical properties and low tensile-compressive asymmetry. Summary of the invention
[0004] The object of the present invention is to provide a high-strength magnesium alloy with improved tensile-compressive asymmetry, which has excellent mechanical properties without adding rare earth elements, low tensile-compressive asymmetry, simple process steps, low preparation cost, and high production efficiency, and a preparation method thereof.
[0005] In order to solve the problems existing in the prior art, the present invention adopts the following technical solutions: A high-strength magnesium alloy with improved tension-compression asymmetry, which, calculated by mass percentage, includes 5.5% to 6.5% Zn element content, 2.5% to 3.5% Bi element content, 0.5% to 0.7% Co element content, less than or equal to 0.5% impurity element content, and the balance is Mg.
[0006] The above-mentioned high-strength magnesium alloy with improved tensile and compressive asymmetry, wherein the Zn element, Bi element, Co element and Mg element are respectively derived from the raw materials single substance Zn, single substance Bi, Co intermediate alloy and pure Mg, and calculated by mass percentage, the purity of the above raw materials is 99.99%.
[0007] A method for preparing a high-strength magnesium alloy with improved tension-compression asymmetry, comprising the following steps: a. Evenly apply appropriate anti-oxidation coating on the inner surface of the crucible, then place the crucible in a pit furnace and preheat it to 200℃~300℃, and place the stainless steel mold for pouring in a resistance furnace and slowly preheat it to 200℃~300℃; b. Weigh the raw materials according to the composition design of the high-strength magnesium alloy, and perform surface treatment on the weighed raw materials until the surface presents a metallic luster, and then put pure magnesium, Co master alloy, single element Zn, and single element Bi into the resistance furnace for preheating in sequence, the preheating temperature is 200℃~300℃, and the preheating time is 1h~2h; c. Heat the pit furnace to 470°C to 500°C, put the pure magnesium preheated in step b into the crucible, and start to pass the protective atmosphere mixed gas. After the magnesium ingot is completely melted, add the Co master alloy, the elemental Zn, and finally the elemental Bi, and then heat it to 720°C to 740°C and keep it still for 10 to 15 minutes; d. Add the refining agent to the melt of step c and stir continuously. After the refining agent is added, keep the mixture warm for 10 to 15 minutes. After the heat preservation and standing, introduce argon for 10 to 15 minutes for degassing. After the degassing, heat the crucible to 740°C to 750°C, and then keep the mixture warm for 10 to 15 minutes. After the second standing, remove the slag, remove the overburned products and impurities on the surface with stainless steel tools, and then let it stand for 10 to 15 minutes. e. Pour the magnesium alloy melt left to stand in step d into a preheated stainless steel mold to obtain a cast magnesium alloy.
[0008] The above-mentioned method for preparing a high-strength magnesium alloy with improved tensile and compressive asymmetry, wherein the protective atmosphere mixed gas is CO 2 and SF 6 The mixed gas, CO 2 and SF 6 The volume ratio is 10:1.
[0009] The above-mentioned method for preparing a high-strength magnesium alloy with improved tensile and compressive asymmetry further includes the following heat treatment steps: a. The obtained cast magnesium alloy is placed in a muffle furnace and heated to 320°C to 340°C for 28h to 30h, then heated to 450°C to 460°C for 12h to 13h for homogenization, then heated to 410°C to 450°C for 1h to 2h, and then immediately placed in an extruder for forward extrusion; b. The extruded alloy obtained by the positive extrusion in step a is water-cooled at 20°C to 25°C for 1h to 1.5h, and the water-cooled extruded alloy is solution treated again at 450°C to 460°C for 2.5h to 3.5h, and then the extruded alloy is placed in an oil bath furnace at 200°C to 220°C for artificial aging for 2.5h to 3.5h.
[0010] The above-mentioned method for preparing a high-strength magnesium alloy with improved tensile and compressive asymmetry comprises the following: the extrusion speed of the forward extrusion is 1.4m / min to 1.6m / min, the extrusion ratio is 44 to 46, the extrusion cavity temperature is 420°C to 440°C, and the mold temperature is 440°C to 460°C.
[0011] In the above-mentioned method for preparing a high-strength magnesium alloy with improved tensile and compressive asymmetry, the surface treatment in step b adopts a mechanical method to remove surface dirt and oxide scale.
[0012] Compared with the prior art, the present invention has the following beneficial effects: a. The present invention provides a new alloy system, which can achieve excellent mechanical properties and improve the tensile and compressive asymmetry of magnesium alloys by adding only a small amount of elements without adding rare earth elements.
[0013] b. The process steps are simplified. High-strength magnesium alloy products can be obtained by hot extrusion and solid solution aging treatment of the cast alloy, which can greatly improve production efficiency.
[0014] c. In terms of performance, the high-strength magnesium alloy product prepared by the present invention has excellent mechanical properties. At the same time, the alloy has low tensile and compressive asymmetry, which expands the application of Mg-Zn alloys. In terms of preparation cost, since the alloy elements are all trace additions and non-rare earth elements, and do not involve complicated process methods and processes, the preparation cost is relatively low; therefore, the new magnesium alloy has the potential for commercial production.
[0015] e. The manufacturing process of the present invention complies with the concept of safety and environmental protection and will not cause any pollution to the environment.
[0016] f. The present invention can recycle products that have exceeded their service life and conduct secondary smelting to save costs while ensuring that the alloy composition deviation and impurity elements meet the regulations. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0018] Figure 1 This is the transmission electron microscope image of 100 nm of Example 1.
[0019] Figure 2 This is the engineering stress-strain curve of room temperature tension and compression after adding 3% Bi (mass fraction) and extrusion + T6 treatment in Example 2 of the present invention.
[0020] Figure 3 The room temperature engineering stress-strain curve of an extruded magnesium alloy to which 3% Bi (mass fraction) is added is comparative example 2 of the present invention.
[0021] Figure 4 This is the room temperature engineering stress-strain curve of an extruded + solid solution magnesium alloy in comparative example 3 of the present invention with 3% Bi (mass fraction) added. DETAILED DESCRIPTION
[0022] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0024] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0025] Unless otherwise specified, the raw materials used in the examples were purchased commercially.
[0026] Example 1 This embodiment provides a high-strength magnesium alloy with improved tension-compression asymmetry, which, calculated by mass percentage, includes 6% Zn element content, 3% Bi element content, 0.6% Co element content, less than or equal to 0.5% impurity element content, and the balance is Mg. The Zn element, Bi element, Co element, and Mg element are derived from the raw materials single substance Zn, single substance Bi, Co master alloy, and pure Mg, respectively, and, calculated by mass percentage, the purity of the above raw materials is 99.99%.
[0027] The Co element can increase the eutectic temperature of Mg-Zn alloys, allowing these alloys to be solution treated at a higher temperature. The higher solution treatment temperature can dissolve more Zn atoms into the magnesium matrix, and at the same time obtain a higher density of vacancies after quenching and water cooling. During the isothermal aging process, the interaction between the high-density vacancies and Zn atoms can promote the aging reaction, thereby making the number density of the precipitated phase of the alloy high and the precipitated phase more dispersed and fine.
[0028] At the eutectic temperature of 553°C, the limiting solid solubility of Bi in the magnesium matrix is 0.13% (mass percentage), while at 200°C the solubility is almost zero, and the Mg precipitated by aging 3 Bi 2 Phase is a high temperature stable phase, which is beneficial to improve the high temperature performance and creep resistance of magnesium alloys. Therefore, Mg-Bi alloys are ideal systems for designing aging strengthening. However, the aging hardening response of binary Mg-Bi alloys is weak. Adding a small amount of Zn to Mg-Bi alloys can significantly increase their aging hardening response, and three different types of Mg are precipitated during aging. 3 Bi 2 phase. Therefore, Bi can be added to Mg-Zn alloys to obtain excellent aging hardening effect. However, high Bi content generally requires sealing with inert gas argon during heat treatment to avoid alloy oxidation during subsequent heat treatment. Therefore, the Bi content added to the alloy of the present invention is not higher than 3% (mass percentage).
[0029] The method for preparing the high-strength magnesium alloy of this embodiment comprises the following steps: Step S1: evenly apply a suitable anti-oxidation coating on the inner wall surface of the crucible, then place the crucible in a pit furnace and preheat it to 300° C., and place a stainless steel mold for pouring in a resistance furnace and slowly preheat it to 300° C.; Step S2: Ingredients: weigh the raw materials according to the composition design of the high-strength magnesium alloy, and weigh 6% of single-substance Zn, 0.6% of Co master alloy, 3% of single-substance Bi, and the rest is pure Mg by mass percentage. The weighed raw materials are subjected to surface grinding by mechanical methods to remove dirt and oxide scale on the surface of the raw materials until the surface presents a metallic luster, and then the raw materials are preheated, and pure magnesium, Co master alloy, single-substance Zn, and single-substance Bi are placed in a resistance furnace in turn, and preheated at 300°C for 1h; Step S3: Melting: The crucible is preheated to 300°C and kept warm for 1 hour, then the crucible temperature is set to 500°C. When the crucible reaches the specified temperature, the preheated pure magnesium ingot is added to the crucible, and a protective mixed gas is passed through. The mixed gas is 10CO 2 :1SF 6 After the pure magnesium ingot is melted, add the Co master alloy, Zn and Bi in turn, then heat to 720℃ and keep it for 15 minutes; Step S4: refining treatment, adding the refining agent to the melt of step S3, stirring the melt continuously during the adding process, and keeping the melt warm and standing for 10 minutes after the adding is completed; Step S5: after the standing still is completed, argon gas is introduced for 10 minutes for degassing; after the degassing is completed, the crucible is heated to 740° C. and allowed to stand for 15 minutes, and after the standing still is completed, the slag is removed, and the overburned products and impurities on the surface are removed using stainless steel tools, and then allowed to stand for 15 minutes; Step S6: Casting: pour the magnesium alloy melt after standing into a cylindrical mold preheated to 300°C to obtain a rod-shaped cast magnesium alloy. The ingot is air-cooled to room temperature. No protective gas is required during the casting process. Note that the casting speed should not be too fast to prevent the formation of a deep riser. Figure 1 This is a transmission electron microscope image of 100nm of the present invention.
[0030] Performance testing: The prepared alloy sample ingots are machined, and the magnesium alloy ingots are processed into the sample shape that meets the corresponding tensile performance test standards, and the performance tests, including tensile performance tests, are carried out. The tensile specimen specifications meet the GB / T16865-2013 standard, and the tensile test method meets the GB / T228.1-2010 standard. The experiment is repeated three times to ensure the accuracy of the data. In the tensile performance test, the yield strength of the alloy is 164Mpa and the tensile strength is 234Mpa.
[0031] Example 2 The difference between this embodiment and embodiment 1 is that it also includes a heat treatment step: The obtained cast magnesium alloy was placed in a muffle furnace and heated to 320°C for 28 hours, then heated to 450°C for 12 hours for homogenization, and then preheated at 420°C for 1 hour, and then immediately placed in a 500t horizontal extruder at 420°C for forward extrusion, with an extrusion rate of 1.5m / min, an extrusion ratio of 45, an extrusion temperature of 420°C, and an extrusion die temperature of 440°C. The extruded alloy obtained by forward extrusion was water-cooled at 20°C for 1 hour, then heated to 450°C again, and allowed to stand for 2.5 hours for solution treatment, and then the alloy was placed in a 200°C oil bath furnace for artificial aging for 3 hours.
[0032] Performance testing: The prepared alloy sample ingots are machined, and the magnesium alloy ingots are processed into sample shapes that meet the corresponding tensile and compression performance test standards, and performance tests are carried out, including tensile performance tests and compression performance tests. The tensile specimen specifications comply with the GB / T 16865-2013 standard, and the tensile test method complies with the GB / T228.1-2010 standard. The compression specimen specifications comply with the GB / T 7314-2017 standard, and the compression test method complies with the GB / T 7314-2017 standard. The experiment was repeated three times to ensure the accuracy of the data. Reference Figure 2 In the tensile performance test, the yield strength of the alloy is 322Mpa and the tensile strength is 344Mpa; in the compression performance test, the yield strength of the alloy is 168Mpa and the compressive strength is 452Mpa. The ratio of the compression and tensile yield strengths of the alloy is calculated to be 0.52.
[0033] Example 3 This embodiment provides a high-strength magnesium alloy with improved tension-compression asymmetry, which, calculated by mass percentage, includes a Zn element content of 6.5%, a Bi element content of 3.5%, a Co element content of 0.7%, an impurity element content of less than or equal to 0.5%, and a balance of Mg. The Zn element, the Bi element, the Co element, and the Mg element are derived from the raw materials, single substance Zn, single substance Bi, a Co master alloy, and pure Mg, respectively, and, calculated by mass percentage, the purity of the above raw materials is 99.99%.
[0034] The method for preparing the high-strength magnesium alloy of this embodiment comprises the following steps: Step S1: evenly apply a suitable anti-oxidation coating on the inner wall surface of the crucible, then place the crucible in a pit furnace and preheat it to 200° C., and place a stainless steel mold for pouring in a resistance furnace and slowly preheat it to 200° C.; Step S2: Ingredients: weigh the raw materials according to the composition design of the high-strength magnesium alloy, and weigh 6.5% of single-substance Zn, 0.7% of Co master alloy, 3.5% of single-substance Bi, and the rest is pure Mg by mass percentage. The weighed raw materials are mechanically polished to remove dirt and oxide scale on the surface of the raw materials until the surface presents a metallic luster, and then the raw materials are preheated. Pure magnesium, Co master alloy, single-substance Zn, and single-substance Bi are placed in a resistance furnace in turn and preheated at 200°C for 2h; Step S3: Melting: After the crucible is preheated to 200°C, the crucible temperature is set to 470°C. When the crucible reaches the specified temperature, the preheated pure magnesium ingot is added to the crucible, and a protective mixed gas is started. The mixed gas is 10CO2 / 60% by volume. 2 :1SF 6 After the pure magnesium ingot is melted, add the Co master alloy, Zn and Bi in turn, then heat to 730℃ and keep it for 10 minutes; Step S4: refining treatment, adding the refining agent to the melt of step S3, stirring the melt continuously during the adding process, and keeping the melt warm and standing for 13 minutes after the adding is completed; Step S5: after the standing still, argon gas is introduced for 13 minutes for degassing; after the degassing, the crucible is heated to 745°C and allowed to stand for 10 minutes, and after the standing still, the slag is removed, and the overburned products and impurities on the surface are removed using stainless steel tools, and then allowed to stand for 10 minutes; Step S6: casting, pouring the magnesium alloy melt after standing into a cylindrical mold preheated to 200° C. to obtain a rod-shaped cast magnesium alloy, and air-cooling the ingot to room temperature. No protective gas is required during the casting process; Step S7: The obtained cast magnesium alloy is placed in a muffle furnace and heated to 340°C for 29 hours, then heated to 455°C for 12.5 hours for homogenization treatment, and then kept at 430°C for 1.5 hours, and then immediately placed in a horizontal extruder at a temperature of 430°C for forward extrusion, with an extrusion rate of 1.6m / min, an extrusion ratio of 46, an extrusion temperature of 440°C, and an extrusion die temperature of 460°C. The extruded alloy obtained by forward extrusion is water-cooled at 23°C for 1.2 hours, and then heated to 460°C again, and solution treated for 3.5 hours, and then the alloy is placed in a 220°C oil bath furnace for artificial aging for 2.5 hours.
[0035] Performance testing: The prepared alloy sample ingots were machined, and the magnesium alloy ingots were processed into the sample shape that meets the corresponding tensile performance test standards, and performance tests were carried out, including tensile performance tests. The tensile specimen specifications meet the GB / T16865-2013 standard, and the tensile test method meets the GB / T228.1-2010 standard. The experiment was repeated three times to ensure the accuracy of the data. In the tensile performance test, the yield strength of the alloy was 319Mpa and the tensile strength was 340Mpa.
[0036] Example 4 This embodiment provides a high-strength magnesium alloy with improved tension-compression asymmetry, which, calculated by mass percentage, includes a Zn element content of 5.5%, a Bi element content of 2.5%, a Co element content of 0.5%, an impurity element content of less than or equal to 0.5%, and a balance of Mg. The Zn element, the Bi element, the Co element, and the Mg element are derived from the raw materials, single substance Zn, single substance Bi, a Co master alloy, and pure Mg, respectively, and, calculated by mass percentage, the purity of the above raw materials is 99.99%.
[0037] The method for preparing the high-strength magnesium alloy of this embodiment comprises the following steps: Step S1: evenly apply a suitable anti-oxidation coating on the inner wall surface of the crucible, then place the crucible in a pit furnace and preheat it to 250° C., and place a stainless steel mold for pouring in a resistance furnace and slowly preheat it to 250° C.; Step S2: Ingredients: weigh the raw materials according to the composition design of the high-strength magnesium alloy, and calculate by mass percentage, weigh 5.5% of single-substance Zn, 0.5% of Co master alloy, 2.5% of single-substance Bi, and the rest is pure Mg. The weighed raw materials are mechanically polished to remove dirt and oxide scale on the surface of the raw materials until the surface presents a metallic luster, and then the raw materials are preheated, and pure magnesium, Co master alloy, single-substance Zn, and single-substance Bi are placed in a resistance furnace in turn, and preheated at 250°C for 1.5h; Step S3: Melting: After the crucible is preheated to 250°C, the crucible temperature is set to 480°C. When the crucible reaches the specified temperature, the preheated pure magnesium ingot is added to the crucible, and a protective mixed gas is started. The mixed gas is 10CO2 / 60% by volume. 2 :1SF 6 After the pure magnesium ingot is melted, add the Co master alloy, Zn and Bi in turn, then heat to 740℃ and keep it for 13 minutes; Step S4: refining treatment, adding the refining agent to the melt of step S3, stirring the melt continuously during the adding process, and keeping the melt warm and standing for 15 minutes after the adding is completed; Step S5: after the standing still is completed, argon gas is introduced for 15 minutes for degassing; after the degassing is completed, the crucible is heated to 750° C. and allowed to stand for 13 minutes, after the standing still is completed, slag is removed, and overburned products and impurities on the surface are removed using stainless steel tools, and then allowed to stand for 13 minutes; Step S6: casting, pouring the magnesium alloy melt after standing into a cylindrical mold preheated to 250° C. to obtain a rod-shaped cast magnesium alloy, and air-cooling the ingot to room temperature. No protective gas is required during the casting process; Step S7: The obtained cast magnesium alloy is placed in a muffle furnace and heated to 330°C for 30 hours, then heated to 460°C for 13 hours for homogenization treatment, and then kept at 440°C for 2 hours, and then immediately placed in a horizontal extruder at a temperature of 440°C for forward extrusion, with an extrusion rate of 1.4m / min, an extrusion ratio of 44, an extrusion temperature of 430°C, and an extrusion die temperature of 450°C. The extruded alloy obtained by forward extrusion is water-cooled at 25°C for 1.5 hours, and then heated to 455°C again, and solution treated for 3 hours, and then the alloy is placed in a 210°C oil bath furnace for artificial aging for 2.8 hours.
[0038] Performance testing: The prepared alloy sample ingots were machined, and the magnesium alloy ingots were processed into the sample shape that meets the corresponding tensile performance test standards for performance testing, including tensile performance testing. The test tensile specimen specifications meet the GB / T 16865-2013 standard, and the tensile test method meets the GB / T 228.1-2010 standard. The experiment was repeated three times to ensure the accuracy of the data. In the tensile performance test, the yield strength of the alloy was 330Mpa and the compressive strength was 350Mpa.
[0039] Comparative Example 1 The difference between this example and Example 2 is that, compared with Example 2, the designed alloy raw material composition does not add Bi element, and calculated by mass percentage, includes 6% of single substance Zn, 0.6% of Co intermediate alloy, and the rest is pure Mg.
[0040] Performance test: The prepared alloy sample ingots were machined, and the magnesium alloy ingots were processed into sample shapes that meet the corresponding tensile and compression performance test standards, and performance tests were performed, including tensile performance test and compression performance test. The tensile specimen specifications conform to the GB / T 16865-2013 standard, and the tensile test method conforms to the GB / T228.1-2010 standard. The compression specimen specifications conform to the GB / T 7314-2017 standard, and the compression test method conforms to the GB / T 7314-2017 standard. The experiment was repeated three times to ensure the accuracy of the data.
[0041] Finally, in the tensile performance test, the yield strength of the alloy was 307Mpa and the tensile strength was 329Mpa; in the compression performance test, the yield strength of the alloy was 119Mpa and the compressive strength was 422Mpa. The ratio of the compression to tensile yield strength of the alloy is 0.39.
[0042] This example shows that the magnesium alloy without adding Bi element has lower yield strength and tensile strength of tensile properties, as well as yield strength and compressive strength of compressive properties than the alloy prepared in Example 2, and the ratio of compressive and tensile yield strengths of the alloy is also lower than that in Example 2. It shows that the alloy design in the present invention does improve the mechanical properties and tensile-compressive asymmetry of the alloy.
[0043] Comparative Example 2 The difference between this example and Example 2 is that, compared with Example 2, the alloy is not subjected to solid solution and artificial aging treatment after extrusion.
[0044] Next, the performance test was carried out, and the tensile test specimens of the obtained alloy were subjected to tensile performance test. The tensile specimen specifications conformed to the GB / T 16865-2013 standard, and the tensile test method conformed to the GB / T228.1-2010 standard. The experiment was repeated three times to ensure the accuracy of the data.
[0045] The yield strength and tensile strength of the alloy in the tensile test at room temperature were 187 MPa and 288 MPa, respectively. Figure 3 This example shows that it is necessary to perform solid solution treatment and artificial aging treatment on the alloy after extrusion. Without subsequent solid solution treatment and artificial aging treatment steps, the second phase dynamically precipitated during extrusion makes the number of solute atoms participating in the subsequent aging precipitation very small, so the aging hardening effect is very poor and the alloy strength is not high. Therefore, the present invention performs solid solution treatment and artificial aging treatment again after hot extrusion and water cooling on the alloy.
[0046] Comparative Example 3 Compared with Implementation Example 2, this example did not perform aging treatment after solution treatment. The extruded alloy was heated to 450°C and allowed to stand for 2.5 hours for solution treatment, and no subsequent artificial aging was performed.
[0047] Next, the performance test was carried out, and the tensile test specimens of the obtained alloy were subjected to tensile performance test. The tensile specimen specifications conformed to the GB / T 16865-2013 standard, and the tensile test method conformed to the GB / T228.1-2010 standard. The experiment was repeated three times to ensure the accuracy of the data.
[0048] This example shows that it is necessary to perform subsequent aging treatment on the cast magnesium alloy. Without the subsequent artificial aging treatment step, the yield strength and tensile strength of the alloy in the tensile performance test at room temperature are 210Mpa and 284Mpa respectively. Figure 4 The yield strength and tensile strength are significantly lower than those of the new Mg-6Zn-0.6Co-3Bi magnesium alloy in Example 2.
[0049] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A high-strength magnesium alloy with improved tension-compression asymmetry, characterized in that: Calculated by mass percentage, the Zn element content is 5.5% to 6.5%, the Bi element content is 2.5% to 3.5%, the Co element content is 0.5% to 0.7%, the impurity element content is less than or equal to 0.5%, and the balance is Mg.
2. A high-strength magnesium alloy with improved tension-compression asymmetry according to claim 1, characterized in that: The Zn element, Bi element, Co element and Mg element are derived from raw materials such as single substance Zn, single substance Bi, Co master alloy and pure Mg, respectively. Calculated by mass percentage, the purity of the above raw materials is 99.99%.
3. The method for preparing a high-strength magnesium alloy with improved tension-compression asymmetry according to claim 1 or 2, characterized in that: The following steps are involved: a. Evenly apply the anti-oxidation coating on the inner surface of the crucible, then place the crucible in a pit furnace and preheat it to 200℃~300℃, and place the stainless steel mold for pouring in a resistance furnace and preheat it to 200℃~300℃; b. Weigh the raw materials according to the composition design of the high-strength magnesium alloy, and perform surface treatment on the weighed raw materials until the surface presents a metallic luster, and then put pure magnesium, Co master alloy, single element Zn and single element Bi into the resistance furnace for preheating in sequence, the preheating temperature is 200℃~300℃, and the preheating time is 1h~2h; c. Heat the pit furnace to 470°C to 500°C, put the pure magnesium preheated in step b into the crucible, and start to pass the protective atmosphere mixed gas, and after the magnesium ingot is completely melted, add the Co master alloy and the elemental Zn in turn, and finally add the elemental Bi, and then heat it to 720°C to 740°C, and let it stand for 10 to 15 minutes; d. Add the refining agent to the melt of step c and stir continuously. After the refining agent is added, keep the mixture warm for 10 to 15 minutes. After the heat preservation and standing, introduce argon for 10 to 15 minutes for degassing. After the degassing, heat the crucible to 740°C to 750°C, and then keep the mixture warm for 10 to 15 minutes. After the second heat preservation and standing, remove the slag, remove the overburned products and impurities on the surface with stainless steel tools, and then let it stand for 10 to 15 minutes. e. Pour the magnesium alloy melt left to stand in step d into a preheated stainless steel mold to obtain a cast magnesium alloy.
4. The method for preparing a high-strength magnesium alloy with improved tension-compression asymmetry according to claim 3, characterized in that: The protective atmosphere mixed gas is a mixed gas of CO2 and SF6, and the volume ratio of CO2 to SF6 is 10:
1.
5. The method for preparing a high-strength magnesium alloy with improved tension-compression asymmetry according to claim 3, characterized in that: The following heat treatment steps are also included: a. The obtained cast magnesium alloy is placed in a muffle furnace and heated to 320°C to 340°C for 28h to 30h, then heated to 450°C to 460°C for 12h to 13h for homogenization, then heated to 410°C to 450°C for 1h to 2h, and then immediately placed in an extruder for forward extrusion to obtain an extruded alloy; b. The extruded alloy obtained by the positive extrusion in step a is water-cooled at 20°C to 25°C for 1h to 1.5h, and the water-cooled extruded alloy is solution treated again at 450°C to 460°C for 2.5h to 3.5h, and then the extruded alloy is placed in an oil bath furnace at 200°C to 220°C for artificial aging for 2.5h to 3.5h.
6. The method for preparing a high-strength magnesium alloy with improved tension-compression asymmetry according to claim 5, characterized in that: The forward extrusion has an extrusion speed of 1.4 m / min to 1.6 m / min, an extrusion ratio of 44 to 46, an extrusion cavity temperature of 420° C. to 440° C., and a mold temperature of 440° C. to 460° C.
7. The method for preparing a high-strength magnesium alloy with improved tension-compression asymmetry according to claim 3, characterized in that: The surface treatment in step b uses a mechanical method to remove surface dirt and oxide scale.
Citation Information
Patent Citations
Induction heat treatment method for reducing tension asymmetry of magnesium alloy material
CN103194702A
Magnesium alloy and processing method for improving tension and compression asymmetry of magnesium alloy
CN113249626A
Hot-rolled magnesium-zinc alloy sheet and manufacturing method thereof
CN103710601A
Magnesium alloy sheet and preparation method thereof
CN103725943A
Degradable biomedical Mg-Bi-Zn-Ca alloy and preparation method thereof
CN109778035A